The Role of Student-Teacher Trust and School Well-Being on Student Engagement in High School Students - Diastu, Naufan Rizqianto; Hidayah, Nurul; Yuzarion, Yuzarion (Universitas Negeri Malang, 2023)
This study examines the role of student-teacher trust, school well-being and student engagement in students. This research method uses a quantitative approach with a correlational type of research. The research design is ex post facto. The research respondents were 180 students selected using a stratified random sampling technique. Data was collected using the student engagement scale, student-teacher trust scale, and school well-being scale, which uses the attitude scale of the Likert model. The data analysis method in this research uses multiple linear regression analysis. The results of multiple linear regression analysis in this study show an F value of 278.134 with a significance level (p) of 0.000 (p less than 0.01). The research results show that studentteacher trust and school well-being on student engagement effectively contribute 75.9 percent to students. Student-teacher trust has a positive role in student engagement, with an effective contribution of 20.25 percent. In addition, there is also a positive role for school well-being towards student engagement, with an effective contribution of 55.64 percent. The conclusions that can be drawn from the research show that there is a very significant role for student-teacher trust and school well-being towards student engagement. The conclusions that can be drawn from the research show that there is a very significant role for student-teacher trust and school well-being in student engagement.